Influence of Low Ag Doping on Structural, Morphological and Optical Properties of Sol-Gel Dip-Coated Nanostructured ZNO Thin Films - Dehimi, M; Touam, T; Chelouche, A; Boudjouan, F; Bouasla, A; Djouadi, D; Fischer, A; Boudrioua, A; Doghmane, A (International Journal of Natural Sciences Research, 2016)
In the present study, a sol-gel dip-coating process was used to deposit almost stress free highly c-axis oriented nanostructured ZnO thin films on glass substrates. The effects of low silver doping concentration (Ag ˂ 1 at.%) on the structural, morphological and optical properties of such films were investigated using different characterization techniques. X-ray diffraction (XRD) measurements have revealed that all the ﬁlms were single phase and had a hexagonal wurtzite structure. The grain size values were calculated and found to be about 24-29 nm. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) images have shown that film morphology and surface roughness were influenced by Ag doping concentration. Optical properties such as transmittance and optical bandgap energy (Eg) were examined using UV-Visible spectrophotometry. The results have indicated that all the prepared ﬁlms were highly transparent with average visible transmission values ranging from 80% to 86%. Moreover, it was found that the Ag contents leads to widening of the bandgap.